Декоративні інтродуценти природної флори в техногенному мегаполісі Донецьк-Макіївка - Glukhov, O.Z.; Prokhorova, S.I.; Derevyanska, G.G.; Kharkhota, G.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Species composition of ornamental alien plants from aboriginal flora (154 species of vascular plants) intentionally attracted from natural habitats into the anthropogenic megalopolis Donetsk-Makeevka was first found and analyzed. This way of primary introduction for plant cultivation in new man-made conditions was treated as spontaneous, intentional or amateur introduction. Bioecological and coenotic analyses of the species composition are performed; groups are allocated on the basis of ornamental features, florescence periods, and frequency of occurrence within the anthropogenic megalopolis, and the group of rare and protected species is separated. It is indicated that ornamental plants of native flora, which were spontaneously introduced into the Donetsk-Makeevka megalopolis gardening, perform aesthetic and sanitation functions as well as have show, cognitive, and educational values.